Surface Analysis of Bacterial Cellulose Membrane Made from Biowaste Added with ZnO Nanopowder - Amasda, Naufal Rizky; Suryanto, Heru; Yanuhar, Uun; Aminnudin, Aminnudin; Nusantara, Fajar; Sias, Quota Alief (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Utilization of pineapple biowaste is important to increase the value added to biowaste and solve the environmental problem. So, the study objective is to synthesize membranes of bacterial cellulose made from pineapple biowaste and characterize the surface morphology and porosity of the membrane after being added with ZnO nanopowder. The study starts with extracting biowaste as a bacterial cellulose culture medium for the fermentation process. The obtained pellicle was crushed and homogenized with the added ZnO nanopowder in the presence of ultrasonic waves. The membrane is dried in the oven. The membrane morphology was monitored using scanning electron microscope and Brunauer–Emmett–Teller analysis. Results indicate that surface morphology more rougher in line with increasing ZnO nanopowder content. The control membrane exhibits the highest surface area (36.9605 m²/g) due to its uninterrupted porous network. The addition of ZnO nanopowder at 2.5% significantly reduces the surface area to 2.9168 m²/g, likely due to nanoparticle-induced pore obstruction. As the ZnO nanopowder concentration increases to 5% and 7.5%, the specific surface area rises to 8.0436 m²/g and 13.7783 m²/g, respectively. This trend suggests that higher ZnO nanopowder loading enhances porosity and introduces additional adsorption sites. The control BC membrane exhibits the highest pore volume and well-defined mesoporosity, which are diminished upon the initial addition of ZnO nanopowder.